OP0206 Performance of SLEDAI-2K to detect a clinically meaningful change in SLE disease activity: a 36-month prospective cohort study of 334 patients. (15th June 2017) - Jesus, D; Rodrigues, M; Matos, A; Henriques, C; Silva, J da; Inês, L
Abstract : Background: The Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) is the core determinant of response in the SLE Responder Index (SRI), a primary efficacy outcome in SLE clinical trials. However, SLEDAI is unable to discriminate partial improvement/worsening, as it scores each item categorically. Furthermore, potentially severe lupus manifestations, such as hemolytic anemia are not scored in SLEDAI. Objectives: To evaluate the performance of SLEDAI-2K to detect a clinically meaningful change in SLE disease activity. Methods: Prospective cohort study of SLE patients followed at a tertiary care lupus clinic from January 2014 to December 2016. Consecutive patients fulfilling the ACR'97 and/or the SLICC'12 classification criteria were included. At each outpatient visit, disease activity from the last 30 days was scored in the Physician Global Assessment (PGA) (0–3 cm scale) and in SLEDAI-2k. The association between PGA and SLEDAI-2K at each visit was tested with Spearman's Correlation. A clinically meaningful change in SLE disease activity was defined as difference in PGA ≥0.3 cm at follow-up compared to the baseline visit. Performance of change in SLEDAI-2K was tested in two models: against worsening and improvement in PGA ≥0.3 cm from baseline using Receiver Operating Characteristic (ROC) curve analysis. Sensitivity, specificity, positive and negative predictive values (PPV, NPV) of SLEDAI-2k to change in PGA was calculated. Statistical significance was set at 0.05. Results: We included 334 patients (87.1% female, mean age at baseline - 44.8±14.5 years). At baseline, median PGA and SLEDAI-2k score was 0.2 points (range 0–2.5) and 2 points (range 0–19), respectively. Eighty-three patients (24.8%) had a PGA ≥0.4 points at baseline. During follow-up of 36 months, 2129 visits were performed. PGA and SLEDAI-2K scores presented a high correlation (rho=0.82, p<0.0001) (fig. 1 ). Reductions in SLEDAI-2K presented in ROC analysis an area under curve (AUC) of 0.697 [95% CI (0.628–0.766), p<0.0001] for an improvement in PGA≥0.3. For a worsening of PGA≥0.3 points, increase in SLEDAI-2K presented an AUC of 0.877 [95% CI (0.822–0.932), p<0.0001]. Estimated sensitivities, specificities, PPV and NPV are presented in table 1 . Conclusions: SLEDAI-2K presents a limited performance in detecting a clinically meaningful change in SLE disease activity, failing to identify more than a quarter of cases with clinically meaningful improvement or worsening. There is a need to optimize SLE disease activity measures. Disclosure of Interest: None declared